EVALUATING THE OUTCOMES OF POSTPARTUM INFECTIOUS COMPLICATIONS IN IRAQI WOMEN - Al-Azzawi, Wasan Faisal Rashid; Abbas, Fadia Mijbil; Alkharkushi, Hend Raheem Abdelhamze (Journal of Medical Genetics and Clinical Biology, 2024)
Background: In the United States, there is not enough new data about how many infections after birth happen or how likely certain problems will be if they occur. In Germany, some research shows that about 10% of women who die while giving birth are killed by blood poisoning. Objective: This study is interested to determine clinical findings of postpartum infectious complications related to Iraqi women. Patients and methods: 88 women enrolled in different hospitals in Iraq for delivery or postpartum care and they were screened for their vital signs during this period. Any woman with a fever (> 38.0 °C) or body temperature (